The Effect of Discovery Learning on the Mathematical Communication Skills in Class X Students - Daniel Juan Piter Sipahutar; Christa Vony Roulina Sinaga; Rianita Simamora (CV Putra Publisher, 2026)
This study aims to analyze the influence of the Discovery Learning Model on the Mathematical Communication Skills of Class X Students at Sma Negeri 4 Pematangsiantar. The type of research that is being studied is curative research. The research method that is being studied is the research method . In this research, the type of research that is being studied is the Curative Research Design with the type of research design namely Oner Shot Caser Sturdy. This research was conducted at SMA Negeri 4 Permatangsiantar which is located at Jalan Patimura No. 1, Pahlawan, Siantar Timur District, Permatangsiantar City. The reason the researcher chose this location is because research with the subject that the researcher has taken has been carried out at the terrserburt school. This research was conducted in the odd semester of the 2025/2026 academic year. Based on the results of data analysis and discussion, it can be concluded that there is a positive and significant influence of the Discovery Learning learning model on the mathematical communication skills of class X students of SMA Negeri 4 Pematangsiantar. This influence can be seen from the regression equation, namely Y = 60.442 + 1.265X with a regression coefficient of 1.265. By means of the t-test, namely t_hitung>t_tabel = (11.142> 7.169) shows that the significance using the coefficient of determination can be seen that the large influence is 81.6%. Based on the results of the calculation of the coefficient of determination, it shows that the discovery learning learning model on students' mathematical communication skills has an influence of 81.6%..